Placental pathology concerning sudden foetal demise in SARS-CoV-2 positive asymptomatic pregnant female - Kamil Biringer (Palacký University Olomouc, Faculty of Medicine and Dentistry, 2021)
Aims. Coronavirus disease 2019 is responsible for a worldwide increase in morbidity and mortality. The relationship of this infection to mother-to-child vertical transmission has not been elucidated yet. However, recent reports indicate a foetal death rate of up to 3%. Methods. We report a case of sudden pre-term foetal demise in a woman positive for SARS-CoV-2 but asymptomatic, with physiological course of pregnancy. Results. One of the possible explanations of sudden foetal death may be acute placental insufficiency caused by a SARS-CoV-2 placental infection or the development of foetal inflammatory response syndrome (FIRS). Conclusion. Considering the potential risk of foetal demise, questions remain regarding foetal monitoring and the timing of labour and delivery in the second and third trimesters, particularly in asymptomatic or mild maternal SARS-CoV-2 infection. A relevant multidisciplinary team must also be aware of these risks associated with possibly fatal consequences.